The Formation of Religious Institutions and Religious Syncretism as a Compensatory Mechanism in the Social System of Ancient China - Barakhvostov, Pavel (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the formation and transformation of religious institutions in ancient China through an institutional approach, focusing on the role of religion not only as a tool of the state but also as a compensatory mechanism in response to systemic crises. Using a qualitative-historical method and document analysis of primary sources from the Shang, Zhou, and Han periods, as well as secondary scholarly literature, the data were analyzed through institutional theory and comparative historical approaches. The findings reveal two main phases in the development of religion: first, the early phase, characterized by ancestral cults and the concept of the Mandate of Heaven, which reinforced political institutions based on redistribution; second, the transformative phase, when Confucianism, Daoism, and Buddhism evolved into adaptive ethical-philosophical systems in response to social upheaval. These three teachings formed a unique syncretic configuration—Three Teachings Harmony (san jiao he yi, 三教合一)—that functioned as an institutional balancing force in a highly hierarchical society. This study highlights the important role of religious syncretism as an ideological and socio-political balance and proposes that this model explains the continuity of religion in China despite official secularization efforts. The originality of this research lies in its institutional approach to religious history, demonstrating that syncretism in China is not merely cultural but structurally shaped by its redistributive political economy. This study contributes to a deeper understanding of the adaptability of religion in hierarchical societies and offers an analytical framework for religious pluralism in other Eastern contexts.